2017
DOI: 10.1177/2325967116679640
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sex and Fatigue on Biomechanical Measures During the Drop-Jump Task in Children

Abstract: Background:Female athletes have a higher rate of anterior cruciate ligament (ACL) injury than males from adolescence and into maturity, which is suggested to result from sex-specific changes in dynamic movement patterns with maturation. Few studies have studied movement strategies and response to fatigue in children.Purpose:To evaluate the effect of fatigue on biomechanical variables associated with increased risk for ACL injury during a drop-jump (DJ) performance in children.Study Design:Controlled laboratory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 45 publications
2
30
2
1
Order By: Relevance
“…As shown in Table 1, the knee flexion angle increased at initial ground contact, but the knee ROM during the landing phase decreased significantly under muscle fatigue condition. These results are consistent with a previous study, which showed that fatigue resulted in greater knee flexion angles at initial ground contact and less excursion during the landing (Briem et al, 2017). Blackburn and Padua (2009) posited that a larger trunk flexion angle during landing caused larger hip and knee flexion angles; moreover, a landing with the trunk flexion effectively reduced vertical GRF and quadriceps myoelectric amplitude.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As shown in Table 1, the knee flexion angle increased at initial ground contact, but the knee ROM during the landing phase decreased significantly under muscle fatigue condition. These results are consistent with a previous study, which showed that fatigue resulted in greater knee flexion angles at initial ground contact and less excursion during the landing (Briem et al, 2017). Blackburn and Padua (2009) posited that a larger trunk flexion angle during landing caused larger hip and knee flexion angles; moreover, a landing with the trunk flexion effectively reduced vertical GRF and quadriceps myoelectric amplitude.…”
Section: Discussionsupporting
confidence: 92%
“…The biomechanical influence of the landing has a greater effect on the legs of female athletes than of male athletes. Studies have indicated that female athletes exhibit larger knee flexion angles during initial ground contact, less knee angular displacement during the landing, greater vertical GRF and greater posterior GRF, greater anterior tibial shear force, and less total lower extremity energy absorption than male athletes during the landing (Briem et al, 2017). These have been reported as crucial factors influencing the occurrence of ACL injuries in female athletes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cutting maneuvers, biomechanical data collection included bilateral drop jumps and strength testing not included in this report. The methods of data collection are described in detail elsewhere [ 5 ]. An 8-camera motion capture system (Qualisys Corporation, Göteborg, Sweden) sampling at 200 Hz was used.…”
Section: Methodsmentioning
confidence: 99%
“…Landing in its different forms, such as single-leg landing (SLL) [ 5 , 6 , 8 , 9 , 10 ] is frequently used as a motor task during physical activity and is commonly used for studying motor pattern development in addition to dynamic postural stability and injury prevention. Landing, an integral part of sports [ 11 ], is a discrete task with a different beginning and end, without a continuous cyclic pattern [ 12 ].…”
Section: Introductionmentioning
confidence: 99%